2021
DOI: 10.1177/00222194211047633
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Evaluating Treatment Response: Evidence Toward Protracted Response Patterns for Severely Impacted Students With Dyslexia

Abstract: Great strides have been made in the development of effective methods of instruction for children with dyslexia. However, individual response to treatment varies, and weaknesses persist for some students with dyslexia despite otherwise effective instruction. Continued efforts are needed to support the prospective identification of poor response, particularly in routine intervention settings. The current study addressed whether indicators of dyslexia risk as outlined by hybrid diagnostic models predict response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Additionally, the two most important variables that moderate intervention effects were dosage and reading domain. These findings are consistent with other research (Catts & Petscher, 2022;Gaab & Petscher, 2022;Kaye et al, 2022;Middleton et al, 2022) and are important in relation to states' dyslexia handbooks because they showed that the amount of time the student participated in explicit reading instruction (ie, dosage) related to a specific reading skill (i.e., domain) had the biggest effects on student learning. In other words, these results suggest that the best approach to teaching students at risk for, or diagnosed with, dyslexia is to identify the specific reading skill gaps and provide explicit and systematic reading instruction across multiple tiers starting in the Tier 1 general education classroom.…”
Section: Intervention Instead Of Instructionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the two most important variables that moderate intervention effects were dosage and reading domain. These findings are consistent with other research (Catts & Petscher, 2022;Gaab & Petscher, 2022;Kaye et al, 2022;Middleton et al, 2022) and are important in relation to states' dyslexia handbooks because they showed that the amount of time the student participated in explicit reading instruction (ie, dosage) related to a specific reading skill (i.e., domain) had the biggest effects on student learning. In other words, these results suggest that the best approach to teaching students at risk for, or diagnosed with, dyslexia is to identify the specific reading skill gaps and provide explicit and systematic reading instruction across multiple tiers starting in the Tier 1 general education classroom.…”
Section: Intervention Instead Of Instructionsupporting
confidence: 92%
“…Nonetheless, other research has suggested that more detailed information about an individual student's reading deficits and dyslexia symptoms could inform the most effective intervention (Middleton et al, 2022). In a study of 115 elementary students participating in a Tier 3 dyslexia intervention, not all students made the expected reading gains (Middleton et al, 2022). Regression analysis showed that the students' pre-intervention fluency skills, gender, and comorbid attention deficit hyperactivity disorder (ADHD) predicted later reading outcomes better than baseline decoding and rapid naming skills.…”
Section: Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies showed that older children could obtain gains comparable to those of younger students: there is no evidence that older children cannot benefit from specific training [ 27 ]. The authors of a recent study evaluated the impact of causes, correlates, and consequences of dyslexia in predicting the outcome of intervention [ 28 ]. Among potential impact factors was the severity of reading problems.…”
Section: Introductionmentioning
confidence: 99%
“…Although gender ratio was not statistically different between conditions, it is worth mentioning that more boys (10 vs 6) were assigned to the Abilmente intervention. Recent evidence showed a gender role in predicting treatment response in DD (Middleton et al, 2022), with males being better responders. Given that and the rather small sample size, we cannot exclude that a slightly greater number of boys in the Abilmente group contributed to better reading improvements.…”
Section: Discussionmentioning
confidence: 99%